1972
DOI: 10.1017/s0022112072001193
|View full text |Cite
|
Sign up to set email alerts
|

The stability of an incompressible two-dimensional wake

Abstract: The growth of small disturbances in a two-dimensional incompressible wake has been investigated theoretically and experimentally. The theoretical analysis is based upon inviscid stability theory wherein small disturbances are considered from both temporal and spatial reference frames. Through a combined stability analysis, in which small disturbances are permitted to amplify in both time and space, the relationship between the disturbance characteristics for the temporal and spatial reference frames is shown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(58 citation statements)
references
References 12 publications
4
54
0
Order By: Relevance
“…For the S0 case, it was found that localized, non-convective normal-component velocity fluctuations are prominent inside the wake. This aerodynamic feature, which has been both predicted and measured previously [6,7,29], can be considered as a noise source. The distance of predicted by feedback Model A is observed experimentally.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For the S0 case, it was found that localized, non-convective normal-component velocity fluctuations are prominent inside the wake. This aerodynamic feature, which has been both predicted and measured previously [6,7,29], can be considered as a noise source. The distance of predicted by feedback Model A is observed experimentally.…”
Section: Discussionmentioning
confidence: 97%
“…For example, in an experimental study of the flow behind flat plates and cylinders, Mattingly and Criminale [29] observed a localized velocity oscillation, which can only be sustained in the absolute instability region. Koch [30] proposed a global resonance condition in which wake tones can sometimes be emitted.…”
Section: Comparisons Of Wake Development For the Straight And Serratementioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Over the years a theory of spatially developping flows has advanced to the point of addressing fully nonlinear structures in wakes [17,18].…”
mentioning
confidence: 99%
“…A11 quantities used here are normalized with the average velocity (U,+U,)/Z, average density (p,+p,)/2 and the local layer The main result is that when the wake component is present there are two unstable branches as opposed to one in the case of the hyperbolic tangent. These two branches do not have much in common with the "sinuous" and "varicose" modes of instability calculated by Mattingly & Criminale (1972) in the case of pure wakes since the symmetry conditions that exist in the pure wake do not hold here. The stronger branch leads to the usual Kelvin-Helmholtz roll-up patterns observed in shear layers and it is referred to here as the shear layer branch.…”
mentioning
confidence: 86%